Pembuatan Portal Kegiatan Perkuliahan Bagi Dosen Sistem Komputer UNDIP - Dyah Mustika Nency Widowati; Kodrat Iman Satoto; Kurniawan Teguh Martono (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2014)
In any lectures, the lecturer must fill journal lectures. Journal of the activity is used to determine the subject matter of the lecture material delivered. In addition as an evaluation if there is material that has not been delivered. Each journal lectures will be always monitored by the Head of the Department to meet its obligations if the lecturers in teaching or not. In the process of implementation, all lectures still be entered manually using paper. It made less cumbersome and complicates monitoring of the Head of Department to monitor any lectures . So the need for making the portal lectures to assist monitoring and lectures journal entry. Making these lectures portals using PHP programming language and MySQL database . As well as using the waterfall method and blackbox testing . Waterfall method includes user requirements, analysis, design, implementation and testing. Blackbox testing is used to test the program without the test of functional design specifications and program code. Used also Entity Relationship Diagram, Data Flow Diagram and in the design of the information system. The results of the application design in the form of web-based desktop application, which is easier for professors to fill any lectures that have been done , knowing the schedule of lectures and the material that was presented at each meeting. As well as Head of the Department to facilitate monitoring any existing faculty.